Assessment of Some Biochemical Parameters in Iraqi Women with Recurrent Miscarriage - Ruqaya K. Abbas; Amani M. Jasim; Qater Al-nada A. Al-Ibady (Journal of Techniques)
Miscarriage a is pregnancy loss that occurs within the first 23 weeks. The risk factors that increase miscarriage is multivariate. Spontaneous loss of a conception before the 20th week of pregnancy is known as a miscarriage. There are two types of miscarriage: spontaneous and recurrent, one or more sporadic miscarriages affects approximately 25 – 50 percent of all women. Recurrent miscarriage, on the other hand, affects about 1% of couples trying to conceive. There are a number of things that can cause a miscarriage, such as inflammatory and immune system diseases. This study aims to compare the levels of calcium, Zinc, lipid peroxidation (Malondialdehyde), and superoxide dismutase (SOD) in the serum of women who have experienced a miscarriage with those of women who are pregnant and healthy. The study included 140 blood samples of women who suffered from a miscarriage and a healthy pregnant group. Calcium and Zinc were evaluated in serum of miscarriage and healthy control group, serum Malondialdehyde MDA, an indicator of lipid peroxidation, serum SOD, antioxidant enzyme, and superoxide dismutase. The calcium concentration was low in aborted women compared with the healthy pregnant control group. Serum zinc levels were lower in women who had an abortion compared to those who were pregnant and healthy. The level of serum SOD and MDA in aborted women raveled differences significantly compared with the healthy pregnant group, a decrease in the mean level of SOD was noticed in aborted women in contrast to the healthy pregnant group. At the same time, MDA showed it enhanced among the aborted group compared with healthy delivered women.